A review of recent advances in the preparation of polyaniline-based composites and their electromagnetic absorption properties - Lin, Tengfei; Yu, Haojie; Wang, Li; Fahad, Shah; Khan, Amin; Naveed, Kaleem-ur-Rahman; Haq, Fazal; Nazir, Ahsan; Amin, Bilal Ul (Journal of materials science, 2021)
The development of telecommunication instruments and electronic devices caused a number of subtle electromagnetic radiations, which have adverse effects on the equipment and especially the health of humans. To date, in order to reduce the harmful radiations, considerable attention has been given to the microwave absorbers due to their several attributes, such as cost-effectiveness, environmental stability and lightweight. Given that polyaniline possesses all above-mentioned properties, in this review, we mainly focus on preparation methods and application of polyaniline-based composites as microwave absorbers, including polyaniline/carbon material composites, polyaniline/magnetic material composites and polyaniline/carbon material/magnetic material composites, and the mechanisms of electromagnetic (EM) wave dissipation have also been discussed. The polyaniline-based composites are more efficient for microwave absorption due to their unique properties; therefore, they could be considered as good materials for microwave absorbers to hinder the EM radiations.